Effect of vitamin E supplementation on production performances in arsenic exposed goats - DAS, TAPAN KUMAR; MANI, VEENA; KAUR, HARJIT; KEWALRAMANI, NEELAM; BANERJEE, DIPAK (The Indian Journal of Animal Sciences, 2014)
The present study was designed to investigate the effect of vitamin E supplementation on production performances in arsenic fed goats. Crossbred lactating goats (24) were distributed randomly into 4 equal groups (control, T1, T2 and T3) of 6 in each, on the basis of average body weight (36.10 ± 0.11 kg) and milk yield (1.61 ± 0.004 kg/day). The animals in T1, T2 and T3 were given 50 mg/kg dry matter arsenic daily, while in T2 and T3, vitamin E @100 IU and 150 IU/kg dry matter, respectively, was also supplemented additionally for 12 months. Both the arsenic and arsenic plus vitamin E supplementation, did not show any significant effect on dry matter intake, body weight and milk yield. Milk Cu, Zn and vitamin E level remain unaffected due to dietary treatments. Except control, in all arsenic exposed groups, milk arsenic level increased and vitamin E in higher doses showed comparatively less increase in milk arsenic level. It can be concluded from the present study that arsenic exposure in goats resulted no changes in production performances, milk Cu, Zn and vitamin E level but increases the milk arsenic level and concomitant treatment with vitamin E is helpful in reducing the burden of arsenic in milk.